ClpP deficiency attenuates contrast-induced HK-2 cell injury through changes associated with mitochondrial dynamics and apoptosis - Jing Wang; Lei Wang; Liang Xie; Chengchun Tang (PLoS ONE, 2026)
Background Contrast-associated acute kidney injury (CA-AKI) is a renal impairment that occurs after several days of intravascular administration of iodine-containing contrast media. ClpP is a key protease that plays an important role in cellular mitochondrial function. This study investigated the role of ClpP in mitochondrial dynamics and early injury in an in‑vitro CA‑AKI model. Methods mRNA sequencing was performed on HK-2 cells with or without iohexol exposure. Cell viability, mitochondrial dynamics-related protein expression, mitochondrial membrane potential (MMP), and cell apoptosis were assessed by cell counting kit-8, immunoblotting, JC‑1 staining and flow cytometry, respectively. Results Iohexol treatment at 80 mg I/mL reduced HK-2 cell viability to 63.44%, induced mitochondrial fission, inhibited mitochondrial fusion and promoted apoptosis. mRNA sequencing revealed significant upregulation of Opa1 and ClpP gene expression, as well as alterations in proteasome‑related signaling in iohexol-induced HK-2 cell. Western blot analysis further confirmed elevated ClpP protein expression after iohexol exposure. Importantly, ClpP knockdown partially restored MMP, increased Opa1 expression, improved mitochondrial morphology, and alleviated iohexol‑induced apoptosis. Conclusion ClpP deficiency may exert cytoprotective effects against iohexol-induced HK-2 cell injury, at least partly through changes associated with mitochondrial dynamics, partial preservation of MMP, and attenuation of apoptosis. These findings suggest that ClpP may represent a potential molecular target for further investigation in CA-AKI.